2018
DOI: 10.2196/jmir.9245
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators When Implementing Web-Based Disease Monitoring and Management as a Substitution for Regular Outpatient Care in Pediatric Asthma: Qualitative Survey Study

Abstract: BackgroundDespite their potential benefits, many electronic health (eHealth) innovations evaluated in major studies fail to integrate into organizational routines, and the implementation of these innovations remains problematic.ObjectiveThe purpose of this study was to describe health care professionals’ self-identified perceived barriers and facilitators for the implementation of a Web-based portal to monitor asthmatic children as a substitution for routine outpatient care. Also, we assessed patients’ (or the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
1
31
0
3
Order By: Relevance
“…Stevenson and colleagues 35 draw similar conclusions. The findings of our study are in line with van den Wijnaart et al, 36 who demonstrated that web-based monitoring cannot replace face-to-face contacts. Based on our findings, AsthmaTuner was used to collect measured values and self-reported symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Stevenson and colleagues 35 draw similar conclusions. The findings of our study are in line with van den Wijnaart et al, 36 who demonstrated that web-based monitoring cannot replace face-to-face contacts. Based on our findings, AsthmaTuner was used to collect measured values and self-reported symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…The eHealth platform is used in regular pediatric asthma care to monitor asthma control using the validated (childhood) Asthma Control Test ([C]-ACT), and to support self-management with personalized online asthma action plans [ 19 , 20 ]. Details of the eHealth platform have been published previously [ 16 - 18 ]. For this study the platform was expanded with a module for FEV 1 home measurements.…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to develop new perspectives on how to use FEV 1 telemonitoring in the future of pediatric asthma care. To achieve this we combined FEV 1 home monitoring with an online eHealth platform [ 16 - 18 ]. Our main research question was “How do patients, their parents, and HCPs want to make use of FEV 1 home monitoring?” Patients who already used the eHealth platform in regular pediatric asthma care to monitor asthma control with questionnaires received FEV 1 monitoring devices which were integrated in the platform.…”
Section: Introductionmentioning
confidence: 99%
“…Lessons learnt from the study are: to develop the tool from the patient’s perspective; to aim for sustainable implementation from the start and anticipate on what is needed; to involve patients and patient organisations in developing and improving the platform; to create obvious personal benefits for patients, aiming for a WIN – WIN situation; to address barriers for implementation (financial and interoperability) adequately; to provide convincing evidence for added value and cost-effectiveness to health insurance companies, hospitals and governments; to invest in a team with common ambition; to ask for professional help in particular with relation to privacy, information technology, legal contracts and similar; to get out of the comfort zone as a researcher and connect with the national governmental institutions and bodies; and, finally, to expect that the processes will take some time [ 44 ].…”
Section: Introductionmentioning
confidence: 99%